2015
DOI: 10.1080/02701367.2015.1051613
|View full text |Cite
|
Sign up to set email alerts
|

External-Focus Feedback Benefits Free-Throw Learning in Children

Abstract: Future research should continue to incorporate retrospective verbal reports and explore potential causal links between internal attentional focus and self-evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…One particular area of interest would be internal vs. external focus of attention. A study by Perreault and French (2015) showed that an external as compared to an internal focus of attention was significantly better in improving free throw performance in children (n = 28). This study was done with recreational child athletes but observing the effect of a change of attentional focus on elite athletes could be interesting, too, regarding changes on warm-up decrement.…”
Section: Free Throw • Calibration • Nba • Basketball • Warm-up Decrementmentioning
confidence: 99%
“…One particular area of interest would be internal vs. external focus of attention. A study by Perreault and French (2015) showed that an external as compared to an internal focus of attention was significantly better in improving free throw performance in children (n = 28). This study was done with recreational child athletes but observing the effect of a change of attentional focus on elite athletes could be interesting, too, regarding changes on warm-up decrement.…”
Section: Free Throw • Calibration • Nba • Basketball • Warm-up Decrementmentioning
confidence: 99%
“…However, Chow et al did not provide consistent focus of attention instructions within each of the experimental conditions; rather, participants were provided a different set of instructions prior to each jump attempt. Perreault and French (2015) found that children (9 and 11 years) practicing basketball free-throws with externally-focused feedback had a significant learning advantage and reported less self-evaluative thoughts and greater goal directed thoughts compared with participants who had received internal-focus feedback. However, Perreault and French (2016) did not find any benefit between internal and external focus instructional FOCUS OF ATTENTION AND CHILDREN'S JUMP PERFORMANCE 7 conditions for children learning a basketball free-throw task, and manipulation checks revealed that use of attentional focus cues was low.…”
mentioning
confidence: 90%
“…In two experiments, asking performers to reflect on their task-related experience resulted in degraded performance (Experiment 1) or learning (Experiment 2) relative to the control condition (Figure 7). A study by Perreault and French (2015) provides additional preliminary evidence for the self-invoking trigger hypothesis. Children between the ages of 9 and 11 years practiced basketball free-throws and were given internal-or external-focus feedback.…”
Section: Mechanisms For Attentional Focus Effectsmentioning
confidence: 99%